2022
DOI: 10.3390/jcm11030525
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Telomerase Reverse Transcriptase Single Nucleotide Polymorphism in Sleep Bruxism

Abstract: Introduction: Sleep bruxism (SB) is a widespread masticatory muscle activity during sleep and affects approximately 13.2% of the general population. Telomerase reverse transcriptase (TERT) plays a role in preventing the shortening of the telomere. This prospective, observational study aimed to investigate the relationship between single nucleotide polymorphism (SNP) of TERT and the severity of SB and to identify the independent risk factors for SB. Methods: A total of 112 patients were diagnosed by performing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The offered explanation was that women are more vulnerable to the effects of unexpected, prolonged stress situations than men [59]. The results of two recent studies are suggesting that the prevalence does not vary between genders [60] or that the male gender was indicated as a risk factor [61].…”
Section: Discussionmentioning
confidence: 99%
“…The offered explanation was that women are more vulnerable to the effects of unexpected, prolonged stress situations than men [59]. The results of two recent studies are suggesting that the prevalence does not vary between genders [60] or that the male gender was indicated as a risk factor [61].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of bruxism is unclear, though recent stu dies reported genetic predisposition for sleep bruxism (SB). 8,9 Additionally, low plasma sodium concentration and inflammatory markers have been associated with SB. 10,11 Moreover, SB has been linked to the motor acti vity of the jaw muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Smardz et al [ 37 ] reported that males exhibited more severe SB than females. Macek et al [ 38 ] reported male sex as an independent risk factor for phasic SB. Guo et al [ 39 ] reported male sex as a risk factor for SB among children 0–12 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not investigate single nucleotide polymorphisms (SNPs) related to SB. Some SNPs (rs2736100, SNP rs6313, rs2770304, rs4941573, and rs2770304) have been reported as risk factors for SB [ 38 , 45 ]. Third, since participants who belonged to the NSB group did not undergo electromyographic observation for SB, we did not compare differences in the numbers of episodes and bursts.…”
Section: Discussionmentioning
confidence: 99%